Comparative Study of Nutritional Status of Children (02-24 Months) with Acute Bronchiolitis and Pneumonia - Shampa, Nazmun Nahar; Mollah, Md Abid Hossain; Billah, Mallick Masum; Kabir, ARM Luthful; Saha, Narayan Chandra (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Acute Bronchiolitis and pneumonia pose significant morbidity and mortality of under five children. This outcome is further influenced by poor nutritional status of the affected child because of depressed immunity. Objective: We sought to evaluate nutritional status of children suffering from acute bronchiolitis and pneumonia in Bangladesh. Methods: This cross sectional study was conducted in the Department of Pediatrics of Dhaka Medical College Hospital and Dhaka Shishu Hospital from July, 2010 to June, 2011. A total of 50 patients of pneumonia aged 2-24 months and 50 patients of acute bronchiolitis of same age were enrolled in this study according to case definitions. After enrolment, the patients were thoroughly assessed with particular emphasis on the anthropometric measurements. Weight, length, MUAC and OFC were measured and recorded in a pretested semi structured questionnaire. For each group Z score of weight for age, weight for length, length for age, OFC and MUAC were calculated. Z score +2 to -1 was defined as normal, -1 to -2 z score as mild poor, -2 to -3 z score as moderate poor and <-3 z score was defined as severe poor status. Results were compared between pneumonia group and bronchiolitis group by using calculated Z value. A calculated Z value more than 1.96 was regarded significant (calculated z value > 1.96 is equivalent to p value< 0.05). Results: Children with pneumonia more often had severe underweight (weight for age <-3 SD) (50% vs. 30%, p= 0.04), microcephaly (OFC <-3SD) (30% vs. 12%, p= 0.03), and low MUAC (<115 mm) (40% vs. 10%, p= 0.03) compared to those with bronchiolitis. Although, there was an increased trend of severe wasting (weight for length <-3 SD) and severe stunting (length for age <-3 SD) in children with pneumonia compared to those with bronchiolitis, the difference was not significant. Conclusion: There thus, the overall nutritional status in children having pneumonia was poor compared to those with bronchiolitis. However, multicenter case control study with larger sample is imperative to consolidate our observation. J Bangladesh Coll Phys Surg 2017; 35(1): 9-14